Language Style Used by Peter Parker in the Spiderman Movie - Sintia, Intan; Savitri, Putu Weddha; Sukarini, Ni Wayan (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2024)
This undergraduate thesis is entitled Language Style Used by Peter Parker in the “Spider-Man” Movie. This study focused on the language style particularly to identify and analyze the type language style and function of language in Peter Parker’s utterances. The object of this study is Peter Parker’s utterances in the “Spider-Man” movie. This study used observation and documentation methods with taking note technique in collecting data. The data was analyzed using descriptive qualitative methods, means the results are explaining descriptively. The results of the analysis are presented in informal method. This study used two theories; the theory of type of language style proposed by Joos and the theory of function of language proposed by Jakobson. Based on the theory, the type of language style in this study shows three types of language style. There are formal style, consultative style, and casual style. In this study, there are types of language style which is not found, namely frozen style and intimate style. These types of language style do not exist because in the movie, the situations and Peter Parker’s utterances does not contain frozen style and intimate style. Meanwhile, the function of language in this study shows four functions of language. There are phatic function, conative function, referential function, and expressive function. There are two functions of language that are not in the movie, namely poetic function and metalingual function because it does not match the contents of the story and Peter Parker’s utterances. The result shows that Peter Parker used more casual style to communicate with other characters and expressive functions, which aimed to express Peter Parker’s emotions and feelings. Keywords: Sociolinguistics, Type of language style, Function of language